2020
DOI: 10.12669/pjms.37.1.3141
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of combination therapy of an Intravitreal injection of bevacizumab and photocoagulation versus Pan Retinal Photocoagulation alone in High risk Proliferative Diabetic Retinopathy

Abstract: Objective: To compare efficacy of intravitreal bevacizumab augmented with Panretinal photocoagulation versus Panretinal photocoagulation alone in high risk proliferative diabetic retinopathy. Methods: This is Randomized clinical control trial study conducted at ISRA University Hospital, Hyderabad from July 2018 to December 2018. A total of 76 eyes were randomized into two groups, 38 eyes undergone PRP plus intravitreal bevacizumab, while 38 eyes had PRP alone. Status of neovessels was assessed before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…However, in the study performed by Jorge, D.M et al, 11 the male:female ratio in group A was 15:20, and 18:17 in group B, respectively. Whereas in the study performed by Rebbeca et al, 12 the male (%) and female (%) in group-A was 58.25 and 41.75, respectively while 62.96 and 37.04 in group B respectively. Further, in the investigation of Darabe, F et al, 13 He, F et al, 14 and Choi W et al, 15 no gender was considered as a prominent isolative factor.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…However, in the study performed by Jorge, D.M et al, 11 the male:female ratio in group A was 15:20, and 18:17 in group B, respectively. Whereas in the study performed by Rebbeca et al, 12 the male (%) and female (%) in group-A was 58.25 and 41.75, respectively while 62.96 and 37.04 in group B respectively. Further, in the investigation of Darabe, F et al, 13 He, F et al, 14 and Choi W et al, 15 no gender was considered as a prominent isolative factor.…”
Section: Resultsmentioning
confidence: 72%
“…However, after 24 weeks of follow-up, the reduction in VH score and BCVA were similar between both treatment strategies. Whereas in the study performed by Rebbeca et al, 12 they observed that, according to the improvement in results of BCVA and timing of regression of neovessels status after combined intravitreal bevacizumab injection and PRP demonstrated that intravitreal bevacizumab is a beneficial adjunctive treatment for high-risk PDR. Though multiple reinjections are required to maintain a visual improvement some patients have regression of retinal neovessels.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…[23] When > 10 studies were identified, the risk www.md-journal.com of publication bias was assessed using a funnel plot of the obtained effect estimates. Overall, the 8 studies corresponded to 6 RCTs [24][25][26][27][28][29] and 2 retrospective studies. [30,31] There were 3 studies compared PRP plus intravitreal bevacizumab with PRP monotherapy, 4 studies compared PRP plus intravitreal ranibizumab with PRP monotherapy, and 1 study compared PRP plus intravitreal aflibercept with PRP monotherapy.…”
Section: Methodsmentioning
confidence: 99%